Routing protocol for battery management system of electric vehicles based on ad‐hoc network. Issue 5 (1st September 2018) - Song, Jiajia; Zhang, Jinbo; Fan, Xinnan
Abstract : The comprehensive performance of electric vehicles (EVs) and distribution of charging locations are two key factors restricting the development of EVs. An effective way to improve the performance of EVs is to manage the battery pack with a battery management system (BMS), while in the actual operation, the collection and analysis of the battery state parameters is of great significance to the study of BMS. It is necessary to detect and provide the location information of the nearest charging station, thus each vehicle is required to have network communication function because the vehicles may move in real time. The ad‐hoc technology is used to solve the network communication between the vehicles and the charging piles. There is no standard routing protocol for ad hoc, and the network routing protocol directly determines the efficiency, reliability and correctness of the network data transmission. Based on the cluster‐tree and ad‐hoc on‐demand distance vector junior (AODVjr) protocols, this study proposed a routing protocol suitable for mobile ad‐hoc network algorithm, and made a simulation on the NS2 platform. The results showed that compared with other protocols, the ad‐hoc routing protocol is more suitable for the application of this system.